La música fusión, ¿verdadera inclusión? Una exploración de la escena fusión en Lima - Montero-Diaz, Fiorella (2018)
In recent years, intercultural popular fusion music in Lima has grown into a representative «national» genre where intersocial and interethnic interactions take place challenging the established segregation of Peruvian society. This music seems to provide a space where youths contest their historical antagonistic role in Lima looking for cultural transcendence and spiritual meaning, searching for their own popular tradition, their own sacred, themselves.Based on diverse case studies, this article explores the sometimes contradictory discourses of fusion musicians when describing their music, as well as the issues they highlight as important to address through their intercultural projects. Moreover, it will examine the potential of fusion music as a means to enable interclass and interethnic interactions, in which the young white upper classes seek to recreate «the self» and include themselves in their own country. Finally, it will document how fusion musicians challenge normalized perceptions and social class imaginaries through the creation of music dialogues. It will explore how the understanding of difference through musicking enables them to search for their own political and spiritual self, which in turn allows them to transcend music and subvert their own class identity in order to experience the «real» Lima, the «New Peru».